Antibiotic long-chain and α,β-unsaturated aldehydes from the culture of the marine fungus Cladosporium sp. - Gallo, Mariana (2004)
Long-chain and α,β-unsaturated aldehydes with antibiotic activity were isolated from the culture of the fungus Cladosporium sp., obtained from an intertidal marine sediment. The structures were determined by spectroscopical methods.